The Marine Knowledge Exchange Network: Insights from an Innovative Regional-to-National Scale Academic-Led Knowledge-to-Impact Network and Recommendations for Future Initiatives. Issue 4 (3rd July 2020) - Johnson, M.T.; Johnson, L.J.; Bayliss-Brown, G.A.; Danino, V.; Day, S.; Dunnett, I.; Forster, J.; Lorenzoni, I.; Kennedy, K.; Malin, G.; Moore, K.; Moore Fuller, P.; et al.
Abstract: This article provides an overview of the approach taken by the Marine Knowledge Exchange Network (M-KEN) and an assessment of its activities in valorizing and generating impact from research. M-KEN was formed in 2014 in response to a call for projects to accelerate impact generated from environmental research in the United Kingdom (UK). M-KEN was university-led and focused in the eastern region of the UK but its approach to fostering impact has had international reach. Over the course of its first five years, M-KEN has leveraged substantial additional funding; spawned numerous spin-off projects; influenced policy and practice; and supported a range of marine research projects in the delivery of their research to stakeholders. This article demonstrates that the reach of M-KEN has been international and has led to substantial ripples of activity radiating out from the core activity of the network. We reflect on the strengths and weaknesses of the approach taken by M-KEN in the context of key research questions around Knowledge Exchange. Finally, we propose recommendations for endeavors from regional to global scale that wish to develop impact from a portfolio of research.